2011
DOI: 10.1037/a0022964
|View full text |Cite
|
Sign up to set email alerts
|

Event-based plausibility immediately influences on-line language comprehension.

Abstract: In some theories of sentence comprehension, linguistically relevant lexical knowledge, such as selectional restrictions, is privileged in terms of the time-course of its access and influence. We examined whether event knowledge computed by combining multiple concepts can rapidly influence language understanding even in the absence of selectional restriction violations. Specifically, we investigated whether instruments can combine with actions to influence comprehension of ensuing patients of (as in Rayner, War… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 50 publications
(172 reference statements)
9
117
3
1
Order By: Relevance
“…Therefore, we can conclude that the typicality effect we found in the experiments should not be considered an effect of semantic anomaly of the low-typicality condition. This corresponds to the point made by Matsuki et al (2011) The typicality effect should also not be considered an effect of priming of the verb by the agent on the patient alone, together with a delayed spillover effect at the target verb: Our materials are well controlled to rule out this possibility, so that both agents selected for each patient can go together with the patient to the same extent (see also the lack of any difference at the patient noun), and every agent appears once as a high-typicality agent and once as a low-typicality agent for a covert event.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, we can conclude that the typicality effect we found in the experiments should not be considered an effect of semantic anomaly of the low-typicality condition. This corresponds to the point made by Matsuki et al (2011) The typicality effect should also not be considered an effect of priming of the verb by the agent on the patient alone, together with a delayed spillover effect at the target verb: Our materials are well controlled to rule out this possibility, so that both agents selected for each patient can go together with the patient to the same extent (see also the lack of any difference at the patient noun), and every agent appears once as a high-typicality agent and once as a low-typicality agent for a covert event.…”
Section: Discussionmentioning
confidence: 84%
“…We created the materials for the self-paced reading experiment using norming studies inspired by the procedures in Matsuki et al (2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel to lexically stored argument structure information, event-related world knowledge also has an important role in rapid language processing (Ferretti, McRae, & Hatherell, 2001;Matsuki et al, 2011;McRae & Matsuki, 2009). That knowledge regarding events or situations resides in semantic memory and is derived from people's experiences with common events, event participants, locations, and other event-related information.…”
Section: Sources Of Information Used In Anticipatory Language Processingmentioning
confidence: 99%
“…A great deal of research indicates that knowledge about real-world events or everyday activities, also called event schemata or script knowledge (Schank & Abelson, 1977), is rapidly activated and influences online processing at the level of individual words (e.g., Chwilla & Kolk, 2005;Hare, Jones, Thomson, Kelly, & McRae, 2009;McRae, Hare, Elman, & Ferretti, 2005), sentences (e.g., Altmann & Kamide, 1999;Bicknell, Elman, Hare, McRae, & Kutas, 2010;Matsuki et al, 2011), and wider discourse (e.g., Camblin, Gordon, & Swaab, 2007;Metusalem, Kutas, Hare, McRae, & Elman, 2012;Otten & van Berkum, 2007). In particular, research on discourse comprehension has shown that event knowledge plays a crucial role in building incremental representations of the situation described in a text, so-called mental or situation models (Johnson-Laird, 1983;Van Dijk & Kintsch, 1983;Zwaan & Radvansky, 1998).…”
Section: Introductionmentioning
confidence: 99%